Comparison of phenolic composition and sensory quality among pear beverages made using Saccharomyces cerevisiae and Torulaspora delbrueckii - He Wenjia; Tian Ye; Liu Shuxun; Vaateri Laura; Ma Xueying; Haikonen Tuuli; Yang Baoru; Laaksonen Oskar (Elsevier, 2025)
The effects of Saccharomyces cerevisiae and Torulaspora delbrueckii on phenolic composition and sensory quality were characterized in the production of alcoholic beverages from selected pear cultivars with diverse biochemical characteristics. The fermentation process generally affected the phenolic composition by increasing the contents of hydroxycinnamic acids and flavan-3-ols and reducing the levels of hydroxybenzoic acids, procyanidins, and flavonols. Although the phenolic compositions and sensory properties of pear beverages depended primarily on pear cultivar selection, the applied yeast strains also played important roles in beverage quality. Fermentation with T. delbrueckii resulted in higher caffeoylquinic acid and quercetin-3-O-glucoside contents, higher rated intensities of ‘cooked pear’ and ‘floral’ odors and a sweeter taste than fermentation with S. cerevisiae. Moreover, higher concentrations of hydroxybenzoic acids, hydroxycinnamic acids, and flavonols correlated closely with astringency perception. Applying T. delbrueckii strains and breeding novel pear cultivars are important approaches to produce fermented beverages of high quality.